Normal-temperature and normal-pressure dried brick-mortar-adhesive biomass aerogel capable of detecting and adsorbing Cr (VI) and application of normal-temperature and normal-pressure dried brick-mortar-adhesive biomass aerogel
The "brick-mortar-binder" biomass aerogel prepared under normal temperature and pressure conditions, using CDs-grafted PAN nanofibers, TOCNFs and CMC, combined with the crosslinking effect of DMTMM, the biomass aerogel preparation problem and the low pollutant removal efficiency in the prior art were solved, and the effect of efficient detection and removal of Cr(VI) was achieved.
Patent Information
- Application Number
- CN202510019545.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to prepare high-performance biomass aerogels by drying at room temperature and pressure, and most of the materials are in powder state, difficult to separate from the solution, easy to cause secondary pollution to the environment, and low detection sensitivity or poor removal performance.
Using carbon quantum dots (CDs) grafted polyacrylonitrile PAN nanofibers, oxidized cellulose TOCNFs and carboxymethyl chitosan CMC as main components, the "brick-mortar-binder" biomass aerogel was prepared through the crosslinking and gelling process initiated by DMTMM to achieve normal temperature and pressure drying.
The prepared biomass aerogel has high sensitivity and strong adsorption ability, which can efficiently detect and remove Cr(VI). Due to the normal temperature and pressure drying process, the mechanical strength of the material is improved, the removal efficiency and detection ability are enhanced, achieving environmental sustainability.
Smart Images

Figure CN119701899A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to a "brick-mortar-adhesive" biomass aerogel dried at room temperature and pressure and its application. Background Art
[0002] As one of the serious environmental pollutants, heavy metal pollution often shows high toxicity, accumulation and non-degradability, posing a serious threat to the ecological environment and human health. Hexavalent chromium Cr(VI), as a typical heavy metal, often appears in industrial wastewater from metallurgy, electroplating and other industries. Due to its carcinogenicity, non-biodegradability and easy bioaccumulation, Cr(VI) poses a major risk to aquatic ecosystems and human health. The World Health Organization has clearly stipulated that the maximum allowable concentration of Cr(VI) in drinking water is 0.05 mg / L. How to sensitively monitor Cr(VI) and remove it from the environment to protect public health is an urgent problem to be solved.
[0003] At present, there are many methods for detecting Cr(VI). Among them, the fluorescence method has the advantages of high sensitivity, fast reaction and strong selectivity, and is an excellent real-time detection method for heavy metals. In 1867, Goppelsroder conducted the first fluorescence analysis and successfully realized the detection of Al 3+ The quantitative detection of Cr(VI) also laid the foundation for the subsequent real-time detection of various pollutants. On the other hand, various methods have been used to remove pollutants, such as physicochemical methods, redox methods and biodegradation methods. The physicochemical method mainly uses porous solid substances as adsorbents to adsorb pollutants on the solid surface and remove them. It has high operability, stable operation and high efficiency. Among them, the adsorption method has the advantages of high removal efficiency, simple operation and green environmental protection. Recently, many researchers have made great efforts to construct materials that can effectively and sensitively detect and remove Cr(VI). For example, Jia et al. prepared lanthanide coordination polymer porous microparticles for detection and adsorption of Cr(VI) [Chem. Eng. J. 2023,457, 141214]. Zhang et al. prepared dual-functional ionic porous organic framework materials for selective adsorption and sensitive determination of Cr(VI) [Sep. Purif. Technol. 2025, 359, 130544]. Although great progress has been made in the detection and removal of pollutants, several major problems still exist: (1) Most materials are in powder form, which is difficult to separate from the solution and easily causes secondary pollution to the environment; (2) The detection sensitivity is low or the removal performance is poor, making it difficult to achieve both high-sensitivity detection and strong removal performance. Therefore, it is of great significance to build a universal platform that can detect multiple pollutants with high sensitivity and strong removal.
[0004] Biomass aerogel made from natural biomass materials is a new type of green and environmentally friendly porous material. It not only exhibits excellent properties that are not inferior to traditional aerogel materials, such as high compressive strength, high elasticity, low apparent density, high porosity and high specific surface area, but also has unique advantages such as a wide range of raw material sources, green and non-toxic, good biocompatibility and biodegradability. Therefore, it has received widespread attention in the fields of energy, environment, electronics and biomedicine. In the traditional preparation methods of biomass aerogel, common preparation techniques such as freeze drying and supercritical fluid drying often have disadvantages such as high energy consumption and high time consumption due to extreme preparation conditions, and the required equipment conditions are relatively strict, which makes it difficult to meet the growing demand for biomass aerogel materials in many fields. Therefore, it is still a challenge to apply new technologies to overcome the disadvantages of aerogel materials in the traditional preparation process while ensuring their excellent physical properties and internal composition structure.
[0005] Drying at room temperature and pressure has mild conditions and simple equipment, and is one of the main research and development directions for low-cost, continuous and large-scale production of biomass aerogels. However, it is a huge challenge to eliminate the capillary force and irreversible shrinkage during room temperature drying, to remove the solvent in the material pores at room temperature and to keep the gel skeleton structure from collapsing, so as to obtain biomass aerogel materials with excellent performance. However, to the best of our knowledge, biomass aerogels prepared by drying at room temperature and pressure have not been found in the field of detection-adsorption. In addition, biomass aerogels dried at room temperature and pressure with excellent mechanical strength are necessary. Therefore, there is an urgent need to develop biomass aerogels prepared by room temperature and pressure for the determination and adsorption of Cr(VI). This will simplify the preparation process, improve mechanical strength, enhance removal efficiency and detection capabilities, and ultimately achieve environmental sustainability. Summary of the invention
[0006] To solve the above problems, the present invention provides a "brick-mortar-binder" biomass aerogel dried at room temperature and pressure to achieve highly sensitive detection and strong adsorption of Cr(VI). The biomass three-dimensional porous aerogel is composed of polyacrylonitrile PAN nanofibers grafted with carbon quantum dots (CDs) as "bricks", oxidized cellulose TOCNFs and carboxymethyl chitosan CMC as "mortar", and triazine derivative DMTMM as "binder". The crosslinking and gelation of TOCNFs and CMC solution are initiated by DMTMM. The method produces a strong hydrogel that can resist capillary forces during environmental volatilization and become an aerogel through freezing, solvent thawing and exchange, and room temperature drying. The present invention provides a novel synthesis scheme for creating biomass aerogels for monitoring and removing heavy metal ions, and lays a foundation for further exploring environmentally friendly and energy-saving materials for environmental remediation in the future.
[0007] The present invention is implemented as follows: first, CDs are prepared by a hydrothermal method, and PAN nanofibers are prepared by electrospinning technology; then CDs@PAN nanofibers (CP) are constructed by a solvothermal method; TOCNFs are prepared by a TEMPO oxidation method; a certain amount of CP, TOCNFs and CMCs are dispersed in water, and DMTMM is added, and then the solution is cross-linked / gelled at 45°C for 3 hours, and then frozen at -20°C for 24 hours to obtain CP / CMC / TOCNF hydrogel, and then thawed in ethanol, solvent exchanged using acetone, and dried at room temperature to prepare CP / CMC / TOCNFs aerogel. Under the optimal process conditions, the CP / CMC / TOCNFs aerogel is prepared in the following steps: (1) Preparation of CDs quantum dots by hydrothermal method 1.98 g PEI and 0.2 g citric acid were dissolved in 60 mL deionized water and stirred for 1 hour at room temperature to ensure complete dissolution. The mixed solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180 °C for 20 hours. The CDs solution was then placed in a dialysis bag for 3 days to obtain CDs. (2) Preparation of PAN nanofiber membrane by electrospinning technology Weigh 0.5 g PAN and dissolve it in 6 mL N,N -dimethylformamide DMF solvent, stirred at 60 ° C for 1 h to obtain an electrospinning solution, 4 mL of the electrospinning solution was added to a plastic syringe with 10 mL, the wire mesh was used as a receiving device, the spinning voltage was 13 kV, the spinning distance was 15 cm, the ambient temperature was 20 ° C-30 ° C, the relative humidity was 20%-50%, and electrospinning was performed. After the electrospinning solution was completely exhausted, the fiber membrane was removed from the wire mesh to obtain a PAN nanofiber membrane; (3) Solvothermal method to construct CP 0.5 g of PAN nanofiber membrane was placed in deionized water and crushed with a homogenizer. Then, the CDs solution was added to the crushed PAN nanofibers and magnetically stirred until a uniform solution was obtained. The mixed solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140 °C for 5 hours. CP was obtained by vacuum filtration. The CP was placed in deionized water and magnetically stirred for 12 hours to remove unreacted substances. These samples were placed in a refrigerator for later use. (4) Preparation of TOCNFs by TEMPO oxidation First, 10 g of bleached hardwood pulp was dispersed in deionized water with a concentration of 1%wt, then 0.16 g of TEMPO and 1.03 g of NaBr were added to the pulp suspension, and then stirred continuously at 800 rpm for 30 min. Subsequently, 65 mL of NaClO was dropped into the solution to initiate the reaction. The pH value was always kept at 10.5. After the reaction, TOCNFs were thoroughly washed with deionized water to remove residual chemicals and finally diluted to a concentration of 1.88%wt. (5) Preparation of CP / CMC / TOCNFs aerogel by drying at room temperature and pressure First, 0.13 g TOCNFs, 1.8 g CMC and 0.2 g CP were dispersed in a certain amount of deionized water, and then 0.09 g DMTMM was added. The solution was then cross-linked / gelated at 45 °C for 3 hours and frozen at -20 °C for 24 hours to obtain CP / CMC / TOCNFs hydrogel. It was then thawed in ethanol and solvent exchanged three times with acetone. The CP / CMC / TOCNFs aerogel was obtained by drying at room temperature and pressure.
[0008] The CP / CMC / TOCNFs aerogel prepared in the above process is light in weight, has a small shrinkage rate, can be prepared in large quantities, and has underwater memory properties; the CP / CMC / TOCNFs aerogel has parallel channels similar to plant ducts, which is conducive to the transportation of liquids, and the CP / CMC / TOCNFs aerogel has good mechanical properties. The CP / CMC / TOCNFs aerogel can still recover to 83% of its original level after 60% deformation and 20 strain loading-unloading cycles without obvious structural collapse and surface cracks; the CP / CMC / TOCNFs aerogel has good fluorescence properties, realizing highly sensitive and highly selective detection of Cr(VI); the CP / CMC / TOCNFs aerogel has a strong adsorption capacity for Cr(VI), achieving the purpose of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a photo of CP / CMC / TOCNFs aerogel standing on a flower and six actual photos of cylindrical aerogels dried at room temperature and pressure; Figure 2 It is the shrinkage variation diagram of CP / CMC / TOCNFs aerogel; Figure 3 This is a photo of the underwater memory performance of CP / CMC / TOCNFs aerogel; Figure 4 This is a SEM photo of CP / CMC / TOCNFs aerogel, which also serves as an abstract figure; Figure 5is the stress-strain curve of CP / CMC / TOCNFs aerogel under 20 compression cycles at 60% deformation; Figure 6 is the SEM photo of CP / CMC / TOCNFs aerogel after compression; Figure 7 are cross-sectional photographs of vertically and horizontally cut CP / CMC / TOCNFs aerogels under sunlight and UV light; Figure 8 is the emission spectrum of CP / CMC / TOCNFs aerogel; Fig. 9 is the emission spectra of CP / CMC / TOCNFs aerogel immersed in Cr(VI) ion solutions with different concentrations; Fig.10 This is the fluorescence intensity relationship diagram of CP / CMC / TOCNFs aerogel under the action of different concentrations of Cr(VI) ions; Fig.11 is the fluorescence intensity diagram of CP / CMC / TOCNFs aerogel under the action of different metal ions; Fig.12 is the adsorption curve of Cr(VI) by CP / CMC / TOCNFs aerogel at different times; Fig.13 This is the adsorption curve of CP / CMC / TOCNFs aerogel at different Cr(VI) concentrations; Fig.14 These are the SEM images and EDS images of CP / CMC / TOCNFs aerogel after adsorption of Cr(VI). DETAILED DESCRIPTION
[0010] The present invention uses polyethyleneimine PEI with a molecular weight of 1800, citric acid, polyacrylonitrile PAN, hardwood pulp, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical TEMPO, NaBr, NaClO, 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholine hydrochloride hydrate DMTMM, potassium dichromate, carboxymethyl chitosan CMC, anhydrous ethanol, N, N -Dimethylformamide (DMF) and acetone were all commercially available analytically pure products; deionized water was homemade in the laboratory; the glass instruments and equipment used were commonly used in the laboratory.
[0011] Example: 1.98 g PEI and 0.2 g citric acid were dissolved in 60 mL deionized water and stirred at room temperature for 1 hour to ensure complete dissolution. The mixed solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and reacted at 180 °C for 20 hours. The solution containing quantum dots CDs was then placed in a dialysis bag for 3 days to obtain CDs. 0.5 g PAN was weighed and dissolved in 6 mL DMF solvent. After stirring at 60 °C for 1 h, PAN / DMF electrospinning solution was obtained. 4 mL of electrospinning solution was added to a plastic syringe with 10 mL. The wire mesh was used as a receiving device. The speed was 13 kV for spinning, the spinning distance was 15 cm, the ambient temperature was 20 °C-30 °C, and the relative humidity was 20%-50%. Electrospinning was performed. After the electrospinning solution was completely exhausted, the fiber membrane was removed from the wire mesh to obtain a PAN nanofiber membrane. 0.5 g The PAN nanofiber membrane was placed in deionized water and broken with a homogenizer. The CDs solution was then added to the crushed PAN nanofibers and magnetically stirred until a uniform solution was obtained. The mixed solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140 °C for 5 hours. The CP was vacuum filtered to obtain the CP, which was placed in deionized water and magnetically stirred for 12 hours to remove unreacted substances. The samples were placed in a refrigerator for standby use. Bleached hardwood pulp (10 g) was dispersed in deionized water with a concentration of 1%wt. TEMPO (0.16 g) and NaBr (1.03 g) were added to the pulp suspension, and then stirred continuously at 800 rpm for 30 minutes. Subsequently, 65 mL of NaClO was dropped into the solution to initiate the reaction. The pH value of the system was always maintained at 10.5. After the reaction, the oxidized cellulose TOCNF was thoroughly washed with deionized water to remove residual chemicals and finally diluted to a concentration of 1.88%wt. 0.13 g TOCNFs, 1.8 g CMC and 0.2 g CP were added. Disperse in a certain amount of deionized water, then add 0.09 g DMTMM, then crosslink / gel the solution at 45°C for 3 hours, freeze at -20°C for 24 hours to obtain CP / CMC / TOCNFs hydrogel; then thaw in ethanol, exchange the solvent with acetone three times, and dry at room temperature to obtain CP / CMC / TOCNFs aerogel. The two CP / CMC / TOCNFs aerogels prepared at room temperature and pressure can stand on a lily petal without causing the lily to deform, and multiple CP / CMC / TOCNFs aerogels can be repeatedly and mass-produced by the same method, which shows that the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has the characteristics of low density, light weight, and mass production, see Figure 1As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure is almost the same as the freeze-dried CP / CMC / TOCNFs aerogel in appearance, and the diameter of the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure is about 27.6 mm, which is almost the same as the diameter of the freeze-dried CP / CMC / TOCNFs aerogel (27.5 mm), indicating that the shrinkage rate of the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure is very small, see Figure 2 As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has underwater memory properties, see Figure 3 As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has parallel channels similar to plant ducts, which is conducive to the transportation of liquids, see Figure 4 As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure can still recover to 83% of its original level after 20 compression cycles under 60% deformation without obvious structural collapse and surface cracks, see Figure 5 As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has obvious parallel channels of plant conduits after compression, and the structure is not clearly damaged. Figure 6 As shown; all cross sections of the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure show the same fluorescence as that observed on its surface, which means that the quantum dots are uniformly dispersed inside and on the surface of the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure, as shown in FIG. Figure 7 As shown; under 360 nm ultraviolet light excitation, the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has an obvious emission peak at 440 nm, see Figure 8 As shown; the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure was tested for Cr(VI) detection performance. As the Cr(VI) concentration (0-500 μM) gradually increased, the fluorescence intensity of the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure gradually decreased. Fig. 9 As shown in Figure 2, the Cr(VI) concentration and the fluorescence intensity ratio of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure I / I 0 There is a good linear relationship between 2 =0.998), where I 0is the fluorescence intensity of the aerogel at 440 nm, I is the fluorescence intensity of the aerogel at 440 nm in different concentrations of Cr(VI) solution, the linear range of Cr(VI) detection by CP / CMC / TOCNFs aerogel prepared at room temperature and pressure is 5-50 μM, and the detection limit (LOD) of Cr(VI) is about 1.14 μM when the signal-to-noise ratio is 3, see Fig.10 As shown; the selectivity of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure was studied. Cr(VI) can cause obvious fluorescence quenching, while other metal ions have little effect on the fluorescence of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure, indicating that CP / CMC / TOCNFs aerogel prepared at room temperature and pressure has a good selective detection effect on Cr(VI), see Fig.11 As shown in the figure; 0.5 g / L of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure was adsorbed in a Cr(VI) solution with an initial concentration of 50 mg / L (pH=2, 25°C). As the adsorption time increased, the adsorption amount of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure gradually increased, and the maximum adsorption amount was 165.91 mg / g. The adsorption amount of Cr(VI) increased sharply in the first 60 minutes, reaching 70% of the maximum adsorption amount. This is because the aerogel initially contained a large number of binding sites, which could quickly combine with water and quickly absorb water and heavy metal ions. After entering the slow stage, the reduction in binding sites led to a decrease in the adsorption rate, and finally reached saturation, as shown in the figure. Fig.12 As shown in the figure, 0.2 g / L of CP / CMC / TOCNFs aerogel prepared at room temperature and pressure was adsorbed in different initial Cr(VI) concentration solutions (10-500 mg / L). As the initial Cr(VI) concentration increased, the CP / CMC / TOCNFs aerogel prepared at room temperature and pressure first increased and then tended to saturation. This is because the number of binding sites between aerogel and Cr(VI) is fixed. As the initial Cr(VI) concentration increased, the number of binding sites gradually decreased and finally reached saturation, as shown in the figure. Fig.13 As shown; Cr element was clearly observed after adsorption in CP / CMC / TOCNFs aerogel prepared at room temperature and pressure, see Fig.14 shown.
[0012] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A "brick-mortar-adhesive" biomass aerogel dried at room temperature and pressure for detecting and adsorbing Cr(VI) and its application, characterized in that: It is light in weight, has a small shrinkage rate, can be prepared in large quantities, and has underwater memory properties. It has parallel channels similar to plant ducts, which is conducive to the transport of liquids. It also has good mechanical properties and can recover to 83% of its original level after 60% deformation and 20 strain loading-unloading cycles. It has good fluorescence properties.
2. A preparation technology of a "brick-mortar-adhesive" biomass aerogel dried at room temperature and pressure for detecting and adsorbing Cr(VI) as claimed in claim 1, characterized in that: Quantum dots are used as fluorescent materials, nanofiber CP containing quantum dots is used as reinforcing phase, carboxymethyl chitosan CMC and oxidized cellulose TOCNFs are used as matrices, and a normal temperature and pressure drying process is adopted to prepare a product, which is a CP / CMC / TOCNFs aerogel dried at normal temperature and pressure. The steps are as follows: (1) Preparation of quantum dots by hydrothermal method 1.98 g PEI and 0.2 g citric acid were dissolved in 60 mL deionized water and stirred at room temperature for 1 hour to ensure complete dissolution. The mixed solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180 °C for 20 hours. The CDs solution was then placed in a dialysis bag for 3 days to obtain CDs. (2) Preparation of PAN nanofiber membrane by electrospinning technology Weigh 0.5 g PAN and dissolve it in 6 mL DMF solvent. Stir at 60 °C for 1 h to obtain PAN / DMF electrospinning solution. Add 4 mL of electrospinning solution into a plastic syringe with 10 mL. The wire mesh is used as a receiving device. The spinning speed is 13 kV, the spinning distance is 15 cm, the ambient temperature is 20 °C-30 °C, and the relative humidity is 20%-50%. Electrospinning is performed. After the electrospinning solution is completely exhausted, the fiber membrane is removed from the wire mesh to obtain a PAN nanofiber membrane. (3) Solvothermal method to construct CP 0.5 g of PAN nanofiber membrane was placed in deionized water and crushed with a homogenizer. Then, the CDs solution was added to the crushed PAN nanofibers and magnetically stirred until a uniform solution was obtained. The mixed solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140 °C for 5 hours. CP was obtained by vacuum filtration. The CP was placed in deionized water and magnetically stirred for 12 hours to remove unreacted substances. These samples were placed in a refrigerator for later use. (4) Preparation of oxidized cellulose (TOCNFs) by TEMPO oxidation First, bleached hardwood pulp (10 g) was dispersed in deionized water with a concentration of 1%wt, and then TEMPO (0.16 g) and NaBr (1.03 g) were added to the pulp suspension, followed by continuous stirring at 800 rpm for 30 min. Subsequently, 65 mL of NaClO was dropped into the solution to initiate the reaction. The pH value of the system was always maintained at 10.
5. After the reaction, TOCNF was thoroughly washed with deionized water to remove residual chemicals and finally diluted to a concentration of 1.88%wt. (5) Preparation of CP / CMC / TOCNFs aerogel by drying at room temperature and pressure First, 0.13 g TOCNFs, 1.8 g CMC and 0.2 g CP were dispersed in a certain amount of deionized water, and then 0.09 g DMTMM was added. The solution was then cross-linked / gelated at 45 °C for 3 hours and frozen at -20 °C for 24 hours to obtain CP / CMC / TOCNFs hydrogel. It was then thawed in ethanol, solvent exchanged with acetone three times, and dried at room temperature to obtain CP / CMC / TOCNFs aerogel.
3. The "brick-mortar-adhesive" biomass aerogel capable of detecting and adsorbing Cr(VI) and dried at room temperature and pressure and its application as claimed in claim 1, characterized in that: Application as detector and adsorbent in wastewater treatment.